(untitled) (Zoological Records and Reviews, 2022)
Cryptic species – morphologically similar but genetically and reproductively distinct lineages – represent one of the most significant and persistent challenges in modern taxonomy and biodiversity science. As molecular tools have become routine in systematic biology, the pace of cryptic species discovery has accelerated dramatically, with estimates suggesting that cryptic diversity may constitute 20-40% of all animal species in morphologically conservative lineages. This review synthesises current knowledge of cryptic species prevalence, identification methods, and taxonomic consequences across five major animal groups – freshwater fishes, amphibians, insects, marine invertebrates, and parasitic helminths – drawing on a meta-analysis of 284 case studies published between 2000 and 2021. Mean cryptic species prevalence across groups is 28.4% of morphologically circumscribed species, with parasitic helminths showing the highest prevalence (42.8%) and marine fishes the lowest (18.4%). Integrative taxonomic approaches combining molecular, morphometric, acoustic, and ecological data demonstrate the highest accuracy for cryptic species delimitation, outperforming single-character methods by 34.8 percentage points. Molecular barcoding (COI) correctly identifies cryptic species in 84.2% of cases when calibrated reference libraries are available. The conservation implications of cryptic diversity are profound: 48.4% of cryptic species identified from nominal widespread taxa qualify as Threatened under IUCN criteria when assessed on their true restricted ranges. We provide a decision framework for practitioners navigating cryptic species identification and recommend minimum standards for evidence required before formal species description.